(untitled) (Res Medica, 2015)
Introduction: Surgical aortic valve replacement (AVR) is the current gold standard treatment for symptomatic aortic stenosis. Without surgical intervention, patients experience a period of rapid clinical worsening, with 50% mortality within two years. However AVR in itself carries considerable risk and many patients may be considered too high risk and therefore not candidates for surgery. Transcatheter Aortic Valve implantation (TAVI) was conceived in 2002 which showed comparable results to AVR in patient are at high surgical risk. TAVI is indicated for high risk patients and in patients that are contraindicated to surgery. Due to increasing public interest there is demand for TAVI to be used within lower risk patients. This is currently being assessed through the large SURTAVI and PARTNER A trials. Aim: The aim of this review is to appraise the current indications surrounding the use of TAVI in potentially low-moderate surgical risk patients and inform its readers about the history of TAVI and its future direction. This paper also addresses the pathogenesis, epidemiology, management and prognosis of aortic stenosis from the most up to date research studies. Methods: A systematic review was conducted. Databases searched included MEDLINE, Embase, AMED, Science Direct, UPTODATE and the British Journal of Cardiology for papers published from the period of January 1990-present. Combinations of the following terms were used: ‘tavi, ‘transcatheter aortic valve implantation’, ‘aortic stenosis’, ‘treatment of aortic stenosis’, ‘aortic valve replacement’ ‘avr’ ‘Medtronic core valve’ ‘bioprosthetic heart valves’, ‘edward sapien bioprostheis’ and ‘treatment of aortic stenosis’. All papers were from the most up to date sources and all information was cross referenced with NICE guidelines and the UPTODATE database. Results: 37 papers were selected for review. The main findings included: the incidence of aortic stenosis is rising due to advances in medical treatment resulting in an aging population; AVR is the current gold standard treatment for aortic stenosis; TAVI is superior to medical therapy alone; TAVI is indicated in high surgical risk patients and those that are contraindicated to surgery; TAVI is comparable to AVR in high risk patients; studies have shown comparable result comparing TAVI with AVR in low- moderate risk pateints; the wide SURTAVI and PARTNER A trials are currently assessing the use of TAVI in low-moderate risk patients. Conclusions: TAVI has revolutionized an alternative way of thinking towards the management of symptomatic aortic stenosis. TAVI is indicated in patient whom are at high surgical risk and in cases where surgery is contraindicated. AVR remains the gold standard treatment in low-moderate surgical risk patients. TAVI may be considered as an alternative method to surgical AVR following the results of the PARTNER 2 and SURTAVI trials.